VERMICOMPOSTING OF MUNICIPAL SOLID WASTE USING DIFFERENT TYPES OF EARTHWORM SPECIES – A COMPARATIVE STUDY - G.AMARAVATHI; R. MALLIKARJUNA REDDY (International Journal of Pharma and Bio Sciences, 2016)
Earthworms eat many types of organic waste materials and convert them into vermin-compost which is highly valued as a fertilizer because it contains plant-available yet stable nutrients. The optimum environmental conditions such as temperature, moisture, pH, EC etc required for vermin-composting of municipal solid waste with different earthworm species and with different substrates are studied. The study indicates that the addition of soil or cow dung appears to be essential in order to provide favorable medium for the growth of earthworms and microorganisms present in them. The loss in the weight of vermin-compost of municipal solid waste with Eisenia foetida is 62.8% after 60 days of vermincomposting where as the loss in the weight of vermin-compost in the case of Perionyx excavatus is only 51% for municipal solid waste. Out of the four substrates used, MSW with the addition of cow-dung appears to be best substrate for E.foetida whereas MSW with cow-dung and soil are best substrates for P. excavatus. Out of the two earthworm species used P. excavatus is a suitable earthworm to convert the MSW mixed with soil and cow dung into nutrient rich vermin-compost.